2022
DOI: 10.1093/pubmed/fdac130
|View full text |Cite
|
Sign up to set email alerts
|

Training during the COVID-19 pandemic: the experience of public health registrars in the London and Kent, Surrey, Sussex training programme

Abstract: Background Public Health registrars (SpRs) were an important component of the workforce that contributed to the COVID-19 response. This study explores their contribution and the impact the early stages of the pandemic had on their learning and training. Methods Data were collected from SpRs in the London and Kent, Surrey, Sussex training programme between July and September 2020 through a mixture of questionnaires and semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…This sits in congruence with other research with public health Registrars, which found a mixed view amongst another Registrar cohort 1 regarding impact of COVID-19 on learning outcomes. This research also supports our study findings, that remote working has negatively impacted mental wellbeing and opportunities to learn and shadow [ 11 ]. The GMC's 2021 National Training Survey highlighted an increase in burnout amongst trainees across all specialties and a swing towards negative answers to wellbeing questions post pandemic compared to before.…”
Section: Discussionsupporting
confidence: 91%
“…This sits in congruence with other research with public health Registrars, which found a mixed view amongst another Registrar cohort 1 regarding impact of COVID-19 on learning outcomes. This research also supports our study findings, that remote working has negatively impacted mental wellbeing and opportunities to learn and shadow [ 11 ]. The GMC's 2021 National Training Survey highlighted an increase in burnout amongst trainees across all specialties and a swing towards negative answers to wellbeing questions post pandemic compared to before.…”
Section: Discussionsupporting
confidence: 91%